2019
DOI: 10.1021/acs.jpca.9b09024
|View full text |Cite
|
Sign up to set email alerts
|

N719 Derivatives for Application in a Dye-Sensitized Solar Cell (DSSC): A Theoretical Study

Abstract: The primary goal of this investigation is to analyze the influence of the chemical modifications on the electronic structures of N719 derivatives for their use in dye-sensitized solar cells (DSSCs), by employing density functional theory. UV−vis spectra indicate that the electronic configurations are essential to study the absorption of solar irradiation and analyze the charge-transport mechanism between the electron-transport layer (ETL), the electrolyte, and the dye. Open-and closed-shell electronic configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…To do so, we make use of the known ruthenium-based metal-organic dye molecule (N719) [48] as an interfacial layer to passivate NiO x and perovskite surface defects concurrently. Notably, the passivation of NiO x /perovskite interface with dye molecules via solution processing is readily scalable and can have significant commercial relevance.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we make use of the known ruthenium-based metal-organic dye molecule (N719) [48] as an interfacial layer to passivate NiO x and perovskite surface defects concurrently. Notably, the passivation of NiO x /perovskite interface with dye molecules via solution processing is readily scalable and can have significant commercial relevance.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 A DSSC has a layer stack structure with photoanode at the top facing the light source (mesoporous layer of nanostructured semiconductors), dye sensitizer, an electrolyte (redox) followed by a counter electrode. 6 Ruthenium dyes of families (N3: cis-diisothiocyanato-bis (2,2 0 -bipyridyl-4,4 0 -dicarboxylic acid) ruthenium(II); Z907: cis-bis(isothiocyanato)(2,2 0 -bipyridyl-4,4 0 -dicarboxylato) (4,4 0 -di-nonyl-2 0 -bipyridyl) ruthenium(II)); N719:ditetrabutylammonium cis-bis(isothiocyanato)bis(2,2 0 -bipyridyl-4,4 0 -dicarboxylato) ruthenium(II)) 7,8 have performed quite efficiently as sensitizers for the photoanode since long. [9][10][11] However, they require rigorous preparation procedures with several steps and diligently purified via chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium dyes of families (N3: cis ‐diisothiocyanato‐bis(2,2′‐bipyridyl‐4,4′‐dicarboxylic acid) ruthenium(II); Z907: cis ‐bis(isothiocyanato)(2,2′‐bipyridyl‐4,4′‐dicarboxylato)(4,4′‐di‐nonyl‐2′‐bipyridyl) ruthenium(II)); N719:di‐tetrabutylammonium cis ‐bis(isothiocyanato)bis(2,2′‐bipyridyl‐4,4′‐dicarboxylato) ruthenium(II)) 7,8 have performed quite efficiently as sensitizers for the photoanode since long 9‐11 . However, they require rigorous preparation procedures with several steps and diligently purified via chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have reported the application of these ZnO NWs in bio-sensing and hydrogen production (Serrano et al, 2017;Galdamez et al, 2019;Galdámez-Martínez et al, 2020a). Additionally, in previous work, we have reported the theoretical study of the absorption spectra of N719 dye together with the ZnO NWs, and it was found that a particular N719 group showed the best alignment of the bands for the better absorption, charge-transport mechanism, and rate of regeneration (Portillo-Cortez et al, 2019). From that experience, we wanted to start implementing the fabrication of the first photoelectrode prototype based on ZnO NWs grown by the VLS process and their relationship with N719 dye for improved absorption.…”
Section: Introductionmentioning
confidence: 93%
“…O'Regan and Grätzel in 1991 proposed a modern kind of renewable solar technology termed as Dye-sensitized solar cell (DSSC) (O'Regan and Grätzel, 1991) that convert solar irradiation to electricity via a similar process to photosynthesis. In a DSSC device, a dye sensitizer such as N719 dye is one of the most critical parts where the majority of the absorption of incident solar radiation occurs to generate electrons that are injected and transported by an Electron Transport Layer (ETL), and finally, collected by a TCO substrate (Portillo-Cortez et al, 2019). The electrons flow through the external circuit toward the counter electrode.…”
Section: Introductionmentioning
confidence: 99%